Malayan Pit Viper Envenomation and Treatment in Thailand - Tangtrongchitr T (Dove Medical Press, 2021)
Thunyaporn Tangtrongchitr,1,2 Suthimon Thumtecho,1,3 Jiratchaya Janprasert,4 Kitisak Sanprasert,2 Achara Tongpoo,1 Yuvadee Tanpudsa,1 Satariya Trakulsrichai,1,5 Winai Wananukul,1,6 Sahaphume Srisuma1,6 1Ramathibodi Poison Center, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Department of Trauma and Emergency Medicine, Phramongkutklao Hospital, Bangkok, Thailand; 3Division of Toxicology, Department of Medicine, Chulalongkorn University and King Chulalongkorn Memorial Hospital, the Thai Red Cross Society, Bangkok, Thailand; 4Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 5Department of Emergency Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 6Division of Clinical Pharmacology and Toxicology, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Sahaphume Srisuma Tel +66 2201 1682Email boat_ra_ac@hotmail.comIntroduction: The Malayan pit viper (MPV; Calloselasma rhodostoma) is a hematotoxic snake found in all regions of Thailand and many countries in Southeast Asia. Treatment of MPV envenomation varies among facilities due to their capabilities.Materials and Methods: This study was a retrospective review of patients with MPV envenomation who were reported to the Ramathibodi Poison Center from 1 July 2016 to 30 June 2018.Results: Of the 167 patients (median age, 40.5 years; range, 1.3– 87.0 years) bitten by an MPV, the most common bite site was the foot (29.3%). Most patients reached the hospital within 1 hour of being bitten. One-hundred fifty-six patients (93.4%) had local effects from envenomation; 17 patients (10.2%) had severe local complications including necrotizing fasciitis (3.0%) and compartment syndrome (7.2%). Systemic effects such as hemorrhage and abnormal hemostasis occurred in 147 patients (88.0%). Additional effects included abnormal venous clotting time in 123 patients (73.7%), unclotted 20-minute whole blood clotting time in 57 patients (34.1%), low platelet counts (< 50,000/μL) in 29 patients (17.4%), prolonged international normalized ratio (> 1.2) in 51 patients (30.5%), and systemic bleeding in 14 patients (8.4%). The median onset of bleeding disorder was 6 hours. Monitoring for 24, 48, and 49 hours after bite enabled detection of systemic effects in 94.2%, 99.3%, and 100.0%, respectively. Three hundred fifteen courses of antivenin were administered to 144 patients (86.2%). All the patients who received antivenin recovered from bleeding disorder. Only 7.0% of antivenin doses were administered without Thai Red Cross indications. Allergic reactions from antivenin occurred in 34.7% of the 144 patients. One hundred thirty patients (77.8%) received antibiotics, and 32 patients (19.2%) required surgical management, including debridement and fasciotomy.Conclusion: MPV envenomation results in local and systemic effects. Most systemic effects were abnormal clotting test results. Most patients reported onset of bleeding disorder within 48 hours.Keywords: Malayan pit viper, snake venom, hematotoxin, antivenin, onset of abnormality